Adapting RISE: meeting the needs of healthcare workers during the COVID-19 pandemic. (17th November 2021) - Wu, Albert W.; Connors, Cheryl A.; Norvell, Matt
Abstract: The COVID-19 pandemic has placed extraordinary stresses on healthcare workers. Combined with disruptions to daily life outside of work, health care professionals experience a high prevalence of anxiety, depression, acute stress reaction, burnout, and PTSD. Top leaders at Johns Hopkins Medicine appreciated the mission-critical importance of maintaining the well-being and resilience of its essential workers. In March 2020 they asked the Johns Hopkins RISE (Resilience in Stressful Events) peer support program to help organize support for all staff. RISE made several adjustments, including adding virtual encounters to the usual in-person support, training additional peer responders, and rounding proactively on active units. Communication was broadened to reach less visible and lower wage workers. RISE collaborated actively with hospital epidemiology and infection control and began reporting regularly at incident command centre briefings. RISE also began to coordinate efforts with the other helping programs within the institution including the Office of Well-being, Employee Assistance, Spiritual Care, and Psychiatry. The number of calls and staff supported rose sharply. RISE supported over 4226 workers in the first 9 months of the pandemic. The adoption of RISE programs was accelerated at affiliated hospitals, as well as at other hospitals across the country in partnership with the Maryland Patient Safety Center. Experience with large scale disasters predicted correctly that worker distress would increase and persist beyond the initial wave of the pandemic. With subsequent surges of COVID-19, exhaustion and moral distress became nearly universal among workers. It is urgent for institutions to provide mechanisms to help their workers cope with the ongoing crisis and other crises that will inevitably occur in the future.